im getting rele confused on this. ok here is the prob.
equation 1 x+y=5 equation 2 x-2y=-4
Multiply equation 1 by -1.
Add equation 1 to equation 2. The x term cancels. Solve for y.
THEN, put the value of y into either equation and solve for x.
Finally, put the value of x and y into the OTHER equation and see if those values satisfy the equation.
Multiplying Equation 1 by -1 you get:
Adding that to equation 2 you get:
-x -y = -5
+ x -2y = -4
-3y = -9
Divide both sides by -3 and you get
Put that back into either equation and you can solve for x
So x=2, y=3 should be the solutions.
Check this in the other equation, x-2y=-4
2-2(3) = -4
2-6 = -4 why yes it does! :-)